Por uma abordagem crítica e explanatória do discurso - Magalhães, Maria Izabel S. (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2016)
The main purpose of this paper is to discuss the approach adopted in my research of the Rezas and Benzeções (healing speech activities in Brazil). I view discourse as part of specific social conditions that should be taken into account, so I am concerned here with the adequate representation of the healers’ social world. Therefore, I suggest that the investigation of discourse be supported by ethnographic field work and comment on the strategies adopted in my data colletion. A detailed description of the methods is offered. In addition, I argue for the interpretation, critique and explanation of discourse. I propose to follow such and approach by examining local community norms as indicators of participants’ values and ideology.